UPAYA MENINGKATKAN KETUNTASAN BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DI SMPN 3 DEPOK SLEMAN TAHUN PELAJARAN 2012/2013 - Yeni Rahmawati ES (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aims of this research were to increase the mastery learning of student by implementation of cooperative Learning type number head together. The method of the reseacrh was Classroom Action Research. The Instrument of data collection used formatif test sheet and photo documentation. Technique of data analysis used qualitative and quantitative analysis. Based on the results of this research showed that through a cooperative learning type Numbered Heads Together (NHT) can increase student mathematics learning completeness VIID class. Increased mastery learning mathematics student looks from the average value of the class, the average value of the final test grade students cycle known to increase students' mastery learning mathematics in the first cycle was 74.3 to 76.2 in the second cycle. In addition, the number of students who received grades greater than or equal to 75 also increased from the first cycle is 16 students or 50% to 25 students or 78.12%.